PELATIHAN IMPLEMENTASI BAHASA INGGRIS FORMAL KEPADA PETUGAS KEAMANAN GARUDA WISNU KENCANA CULTURAL PARK BALI - Ida Bagus Gde Nova, Winarta,; I Gusti Bagus Wahyu Nugraha, Putra,; Kadek Vivi Nanda Komala, Sari, (Fakultas Bahasa Asing, 2024)
Garuda Wisnu Kencana Cultural Park is a tourism destination located in Ungasan, South Kuta, Bali. The pandemic which happened in 2020 has caused many workers. The pandemic that occurred in 2020 had caused the closure of tourist attractions which forced many workers to be laid off. When the tourism sector reopens, many tourist destinations have to recruit employees on a large scale. This has an impact on the human resources of the employees who have been recruited, especially their foreign language skill on English. This article aims to portray the results of formal English implementation training on Garuda Wisnu Cultural Park Bali’s security officers. The method that is applied in doing the training is direct learning, using a theory proposed by Hunaepi, Taufik Samsuri, and Maya Afrilyana (2014). The training is done by some steps which is doing a pre-test, giving direct materials, and final test. Qualitative method is used in analyzing the data. Formal and informal method are used in presenting the findings. It is found that the average score is 65 from the pre-test. After the materials has been given, the average score of the security officers from the final test is 83.